ANALISIS LAPORAN KEUANGAN SEBAGAI ALAT UNTUK MENGUKUR KINERJA KEUANGAN PADA KOPERASI TIGA KOTO SIMPAN PINJAM (KSP) DESA SIBIRUANG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - Mimi Adillah; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Cooperatives are a people's economic movement that has duties and responsibilities, in terms of the welfare of all members through the fulfillment of all appropriate and adequate needs. The purpose of this study was to determine the financial performance of the Three Koto Savings and Loans Cooperative (KSP) in Sibiruang Village, Koto Kampar Hulu District, Kampar Regency in terms of the financial ratios used. The location of this study was conducted at the Tiga Koto Simpan Pinjam (KSP) Cooperative in Sibiruang Village, Koto Kampar Hulu District, Kampar District. Ratio analysis used in this study is the liquidity ratio, profitability, solvency, capital and efficient salary. The method used is quantitative descriptive analysis. Based on the results of the research in terms of the liquidity ratio of the Tiga Koto Cooperative in Siberuang Kampar Village, it is good in terms of asset likuidity ratio, loan to total assets and loan to deposit ratio. From the solvability side of the Tiga Koto Cooperative in Siberuang Kampar Village, it has also been categorized both in terms of liabilities to total assets, and time interest earned. While profitability is still not good because the cooperatives are still not using the assets they have to increase the remaining business results, both measured by return on assets. While in terms of return on equity and net profit margin, it has been in the good category. And the capital ratio produced at the Tiga Koto Cooperative in Siberuang Kampar Village where the equity ratio of total assets is good. While the equity to total loan ratio in the category is not good because it exceeds the standard value of 20%. And the business efficiency ratio where it is already in good condition, especially the ratio that describes the ability of income generated in closing the salary burden of its employees.Keywords: Financial Ratio, Cooperative Performance, Liquidity Ratio, Profitability, Solvability, Capital and Efficient Salary